(untitled) (Journal of Engineering, 2025)
The relationship between cinema and architecture has witnessed an increasing presence in contemporary studies, as both converge at a common point: shaping human experience within a specific temporal and spatial space. Cinema uses the principles of rhythm, sound, and memory to shape visual and auditory narratives, while architecture seeks to embody these principles in tangible spaces that organize human movement and influence sensory and emotional perception. This relationship demonstrates that cinematic expression tools can enrich architectural experience. However, the challenge lies in the limited theoretical frameworks that explain how to translate these principles into design strategies, particularly in cultural architecture. Based on this gap, this research aims to explore the principles of rhythm, sound, and memory as tools capable of reshaping the architectural experience and enhancing the user’s perception of space. To achieve this, the research relied on a qualitative analysis of international case studies that included the Jewish Museum in Berlin, the Paris Philharmonic Hall, and the Teshima Art Museum, tracing the roles of the three principles: rhythm in organizing movement, sound in shaping spatial atmosphere, and memory in building emotional connections within architectural narratives. The results reveal that integrating these principles contributes to enriching sensory perception and deepening emotional responses. They also demonstrate that aligning cinematic logic with architectural design provides a multidisciplinary framework for rethinking the narrative of space. Thus, the research presents an innovative approach to employing cinematic tools in cultural architecture, creating immersive spaces that stimulate the senses, evoke memory, and enhance human presence.